Periareolar Approach in Oncoplastic Breast Conservative Surgery. Issue 4 (18th April 2016) - Klinger, Marco; Giannasi, Silvia; Klinger, Francesco; Caviggioli, Fabio; Bandi, Valeria; Banzatti, Barbara; Forcellini, Davide; Maione, Luca; Catania, Barbara; Vinci, Valeriano; Lisa, Andrea; Cornegliani, Guido; et al.
Abstract: Breast cancer represents the most frequent cancer in female population. Nowadays breast conservative surgery (BCS) is an accepted option for breast malignancies, and its indications has been extended thanks to the advent of oncoplastic surgery, reducing both mastectomy and re‐excision rate, avoiding at the same time breast deformities. From January 2008 to November 2011, 84 women underwent BCS with periareolar approach for oncoplastic volume replacement. We divided patients into four groups analyzing breast size and resection volume (Group 1: small‐moderate sized breast with resection <20%; Group 2: small‐moderate sized breast with resection >20%; Group 3: big sized breast with resection <20%; Group 4: big sized breast with resection >20%). We evaluated patients' satisfaction regarding final esthetic outcome using the specific module "Satisfaction with outcome" of the Breast‐Q questionnaire 1 year after surgery. The mean age was 52.1 years, and the mean follow‐up was 11.2 months. During the follow‐up, 12 patients have been lost. We obtained high satisfaction mean value with Breast‐Q questionnaire in each group: 75.8 in group 1, 63.4 in group 2, 81.1 in group 3, 69.7 in group 4. Periareolar approach as oncoplastic volume replacement technique is useful in correction of breast deformity after BCS: it is a versatile technique that can be easily adapted for any breast tumor location and for wide glandular resection.